2006
DOI: 10.1021/ja064355f
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Experimental Electron Density Analysis to Metastable States:  A Case Example of the Spin Crossover Complex Fe(btr)2(NCS)2·H2O

Abstract: An experimental electron density (ED) analysis of the spin crossover coordination complex Fe(btr)(2)(NCS)(2).H(2)O has been performed in the ground low-spin (LS) state and in the metastable thermally quenched high-spin (HS) state at 15 K by fitting a multipolar model to high-resolution X-ray diffraction measurements. The ED has been quantitatively analyzed using the quantum theory of atoms in molecules. This is the first time the ED distribution of a molecular metastable state has been experimentally investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 61 publications
(76 reference statements)
3
34
0
Order By: Relevance
“…This contraction is known to be associated with the electronic population of more bonding states in the LS electronic distribution, as observed by electron density analysis. 50 Therefore the two polymorphs have the same average Fe-N bonds in the two HS (high-temperature or photoinduced) and LS states. Differences are observed by looking at the deformation of the Fe-N 6 octahedron, through the angular distortion parameter 39,51 and on the length distortion parameter ζ [see geometry are similar and small in the LS state, the molecular HS state of BIA I appears significantly more distorted than the one of BIA II, both for the HS stable state above 170 K and the photoinduced one at low temperature.…”
Section: Detailed Crystallographic Analysis During Thermal and Pmentioning
confidence: 98%
“…This contraction is known to be associated with the electronic population of more bonding states in the LS electronic distribution, as observed by electron density analysis. 50 Therefore the two polymorphs have the same average Fe-N bonds in the two HS (high-temperature or photoinduced) and LS states. Differences are observed by looking at the deformation of the Fe-N 6 octahedron, through the angular distortion parameter 39,51 and on the length distortion parameter ζ [see geometry are similar and small in the LS state, the molecular HS state of BIA I appears significantly more distorted than the one of BIA II, both for the HS stable state above 170 K and the photoinduced one at low temperature.…”
Section: Detailed Crystallographic Analysis During Thermal and Pmentioning
confidence: 98%
“…the mechanism of photoswitching from the molecule to the material scale, the different nature and timescales of the intervening transitions and intersystem crossings, and the lifetime of the final photo-induced state [10]. In particular structural investigations went from the first crystal structure of a sample in the light-induced HS state in 2001 [11] to charge density studies of the metastable state [12] and recent pioneering ultrafast crystallography studies of the photo-induced SCO mechanism [13]. Indeed spectroscopic ultrafast techniques, with a strong feedback of advanced ab initio calculations [14], have been intensively used in the last decade on some simple Fe(II) compounds such as [Fe(bipy) [16] (tpy= 2,2′:6′,2″-terpyridine), taken as models for the photophysical processes in other metal transition complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The success of kind experiments consists in in situ laser irradiation of a cryogenically cooled crystal, with a N2 or He gas-flow system for less restricted access than closed cryostat (White et al, 1994), mounted on a diffractometer equipped with a CCD detector for fast data collection (Graafsma et al, 1997;Muchmore, 1999). More recently, Legrand (2005) has developed a crystallographic experimental methodology approach 2007a;2007b) and shown that it is possible to measure with accuracy photo-induced metastable states and to refine its experimental electron density below 35 K using conventional X-ray sources (Legrand et al, 2006;Pillet et al, 2008).…”
Section: State-of-the-art Sample Environments At Laboratoriesmentioning
confidence: 99%